2011
DOI: 10.1016/j.compbiolchem.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Direct correlation analysis improves fold recognition

Abstract: Graphical abstractHighlights► The problem of protein prediction from sequence is difficult and incompletely solved. ► We show that a new method based on correlated mutations in a multiple sequence alignment, filtered through a process to extract direct contacts provide powerful constraints on selecting the correct fold in a large number of well constructed decoy models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Recently, the application of sparse inverse covariance matrices to contact prediction has led to a significant improvement in the accuracy of such predictions,29–34 raising the possibility of using such predictions as a source of information on possible domain boundaries, an earlier study of which was performed by Rigden 35. In this article, we explore a number of methods to exploit this new information and show that a simple kernel‐smoothing predictor can provide accurate information of use in domain prediction with an improvement of between 8 and 20% over other ab initio predictors.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, the application of sparse inverse covariance matrices to contact prediction has led to a significant improvement in the accuracy of such predictions,29–34 raising the possibility of using such predictions as a source of information on possible domain boundaries, an earlier study of which was performed by Rigden 35. In this article, we explore a number of methods to exploit this new information and show that a simple kernel‐smoothing predictor can provide accurate information of use in domain prediction with an improvement of between 8 and 20% over other ab initio predictors.…”
Section: Introductionmentioning
confidence: 94%
“…Previously, such attempts were hindered, principally, by a lack of sequence data; however, with the recent acceleration in the accumulation of known sequences, this limitation is becoming less of a restriction. Recent attempts to use residue covariation have been based on families of many sequences11 and have met with greatly improved success 12…”
Section: Introductionmentioning
confidence: 99%
“…We have shown in this work that the application of predicted contacts derived from mutual information, can be applied with improved effect to the combinatorial fold generation level of the PLATO model construction method compared with previous results where it was applied only as a post-filter [6]. This entailed using the predicted contacts at the level of secondary structure elements (SSEs) rather than at the residue level.…”
Section: Discussionmentioning
confidence: 99%
“…Using these large sequence families, it now appears that the information in pairwise residue correlations is approaching a threshold at which useful structural constraints can be obtained [6]. In that work, we showed that predicted contacts derived from processing the mutual information (MI) between positions in a multiple sequence alignment could be used to select the correct fold from a large collection of well constructed decoys.…”
Section: Introductionmentioning
confidence: 99%